Development of Science Module SETS Approach to Strengthen Cognitive Learning Outcomes of Elementary School Students - Candra, Rio; Rahayu, Enni Suwarsi; Putra, Ngurah Made Darma (Universitas Negeri Semarang, 2020)
At present, there is still a lack of teaching materials in Elementary Schools, specifically science that is suitable to the needs of students and encourages students to care about their environment. The purpose of this study is to develop a Natural Sciences module with the STSE (Science, Technology, Society, Environment) approach to strengthen cognitive learning outcomes in Elementary Schools. The method used is the research development of the modified Borg and Gall model, namely preliminary studies, development stages, and evaluation stages. The research subjects were grade IV students, Public Elementary School Kangkung 1 Mranggen. Data collection instruments used were observation sheets, tests, questionnaires, and documentation. Analysis of research with t-test and n-gain test to determine the comparison of modules, as well as improvement of learning outcomes. The results of the study that the Natural Sciences module, with the STSE approach, is valid for use. The results of trials with the t-test show the difference between the use of modules and student books, N-gain module usage scores 0.723 with a very high category. The practicality test shows a practical module so that students and teachers can accept it. The Science Module STSE approach can be used as a substitute for teaching material on the theme of the environment around Grade IV Elementary School.